Iconographies for Children and Development of Imaginary: Emblematic Examples - Lepri, Chiara (Studi sulla Formazione/Open Journal of Education, 2016)
The illustration for children is set up as an artistic-narrative language acting with extreme power and incisiveness on the creation of the visual imaginary, whether it be ’simple’ set to the verbal or complementary text, or totally ’unhooked’ from that in the story function, as it happens, for example, in the silent books. Those involved in educational sciences and those who approach children’s literature should probe the illustrator’s point of view, particularly when the latter is shrewd and conscious and, at the same time, freely expresses a remarkable artistic sensitivity in the performance of his/her job.